Actinostoloidea CARLGREN 1932 - Gusmão, Luciana C.; Rodríguez, Estefanía (Zenodo, 2021)
SUPERFAMILY ACTINOSTOLOIDEA CARLGREN, 1932 Diagnosis (after Gusmão et al. (2019) with additions in italics). Enthemonae usually with basilar muscles, mesogleal marginal sphincter and no acontia or acontioids; rarely lacking basilar muscles and marginal sphincter muscle. Aboral end mostly flat and adherent; sometimes with physa. Column usually smooth; rarely with cuticle and rows of tubercles . Mesenteries usually not differentiated into macro- and microcnemes; rarely differentiated into macro- and microcnemes. Mesenteries of same pair often unequally developed. Retractors usually diffuse weak or strong, sometimes circumscribed. Cnidom: gracile spirocysts, basitrichs, holotrichs, b -mastigophores and p-mastigophores A . Included families: Actinostolidae, Exocoelactinidae, Halcampoididae and Halcampulactidae. Remarks: We modified the diagnosis of the superfamily Actinostoloidea to reflect the characters observed in the new species ( Chitinactis marmara e.g. rows of tubercles formed by thickenings of mesoglea and strong cuticle on column). In addition, we modified the superfamilial diagnosis to reflect recent changes in the higher level classification of Actiniaria (i.e. Rodríguez et al. , 2014) and the nematocyst terminology used in this study (see: Gusmão et al. , 2018). These modifications have been made in all other diagnoses included in this study. : Published as part of Gusmão, Luciana C. & Rodríguez, Estefanía, 2021, Two sea anemones (Cnidaria: Anthozoa: Actiniaria) from the Southern Ocean with evidence of a deep-sea, polar lineage of burrowing sea anemones, pp. 1392-1415 in Zoological Journal of the Linnean Society 193 on page 1397, DOI: 10.1093/zoolinnean/zlaa176, http://zenodo.org/record/5752621 : {"references": ["Carlgren O. 1932. Die Ceriantharien, Zoantharien und Actiniarien des arktischen Gebietes. In: Romer F, Schaudinn F, Brauer A, Arndt W, eds. Eine Zusammenstellung der arktischen Tierformen mit besonderer Berucksichtigung des Spitzbergen-Gebietes auf Grund der Ergebnisse der Deutschen Expedition in das Nordliche Eismeer im Jahre 1898. Jena: Gustav Fischer, 255 - 266.", "Gusmao LC, Berniker K, Van Deusen V, Rodriguez E. 2019. Halcampulactidae (Actiniaria, Actinostoloidea), a new family of burrowing sea anemones with external brooding from Antarctica. Polar Biology 42: 1271 - 1286.", "Gusmao LC, Grajales A, Rodriguez E. 2018. Sea anemones through X-rays: visualization of two species of Diadumene (Cnidaria, Actiniaria) using micro-CT. American Museum Novitates 3907: 1 - 45."]}